2020
DOI: 10.1016/j.cell.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diets Alter the Gut Microbiome Resulting in Decreased Intestinal Th17 Cells

Abstract: Highlights d Ketogenic diets (KDs) alter the gut microbiota in a manner distinct from high-fat diets d Gut microbial shifts on KDs are driven in part through host production of ketone bodies d b-hydroxybutyrate selectively inhibits bifidobacterial growth d The KD-associated gut microbiota reduces levels of intestinal Th17 cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
308
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(356 citation statements)
references
References 61 publications
12
308
3
Order By: Relevance
“…We reported changes in the gut microbiota after KD intervention, with increased levels of Ruminococcaceae and Lachnospiraceae, which were positively correlated with glucose intolerance and lipid accumulation. However, a recent study showed that the abundance of Ruminococcaceae and Lachnospiraceae decreased after changing a baseline diet to a ketogenic diet [21]. This discrepancy may have occurred because the experimental subjects in our study were normal mice, whereas those in other studies were overweight or obese people.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We reported changes in the gut microbiota after KD intervention, with increased levels of Ruminococcaceae and Lachnospiraceae, which were positively correlated with glucose intolerance and lipid accumulation. However, a recent study showed that the abundance of Ruminococcaceae and Lachnospiraceae decreased after changing a baseline diet to a ketogenic diet [21]. This discrepancy may have occurred because the experimental subjects in our study were normal mice, whereas those in other studies were overweight or obese people.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous work found that a KD altered the structure of gut microbiota, and speci c KD-associated bacteria could protect against seizures in mouse models of intractable epilepsy, which was further con rmed because the protective effects disappeared when mice were treated with antibiotics or reared germ free [20]. Furthermore, a recent study showed that a KD decreased the abundance of Bi dobacterium, and KD-associated gut microbiota reduced the levels of intestinal proin ammatory Th17 cells [21]. Therefore, whether the gut microbiota altered by a KD affects host glucose and lipid metabolism became an interesting question, as did whether microbial-associated metabolites also play a role.…”
Section: Introductionmentioning
confidence: 88%
“…One prominent example is the ketogenic diet, which aims at biochemically replacing carbohydrates with fat as a primary energy source through consumption of a low-carbohydrate, high-fat diet. This diet is commonly used in clinical practice to reduce seizure frequency in the treatment of drug-resistant epilepsy and is known to induce considerable microbiome and immune alterations; however, its mechanism of action remains unknown (107,108). A recent study demonstrated that the ketogenic diet lacks an antiseizure effect in microbiome-depleted mice (either GF or antibiotic-treated mice) and that a fecal microbiome transfer from mice fed a ketogenic diet into mice fed a control diet induced a seizure-protective effect (109).…”
mentioning
confidence: 99%
“…187,188 Recent studies suggest a casual pathway wherein the ketone body BHB suppresses the growth of specific immunomodulatory members of the human gut microbiota (Bifidobacterium sp), leading to a decrease in small intestinal lamina propria T H 17 cells. 189 More work is needed to explore the mechanisms through which BHB impacts gut bacterial growth, host-microbiome interactions within the intestinal mucosa, and the broader consequences of these observations for systemic inflammation.…”
Section: Ll Bhb Alters Gut Microbiome To Modulate Inflammationmentioning
confidence: 99%